2022
DOI: 10.1007/s40519-022-01452-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors of screen-based disordered eating among university students: a global systematic review, meta-analysis, and meta-regression

Abstract: Purpose The purpose of this review was to estimate the prevalence of screen-based disordered eating (SBDE) and several potential risk factors in university undergraduate students around the world. Methods An electronic search of nine data bases was conducted from the inception of the databases until 1st October 2021. Disordered eating was defined as the percentage of students scoring at or above established cut-offs on validated screening measures. Global data were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 182 publications
3
15
2
Order By: Relevance
“…The prevalence of ED risk as measured by EAT-26 varies greatly with age, gender, and region in which the study is conducted. Most contemporary reviews and meta-analyses are based on samples of university and college students [85,86] . In the only cross-cultural study [87] involving female students from Russia and Japan, 8.6% of the Russian respondents and 7.9% of the Japanese respondents appeared at risk.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ED risk as measured by EAT-26 varies greatly with age, gender, and region in which the study is conducted. Most contemporary reviews and meta-analyses are based on samples of university and college students [85,86] . In the only cross-cultural study [87] involving female students from Russia and Japan, 8.6% of the Russian respondents and 7.9% of the Japanese respondents appeared at risk.…”
Section: Discussionmentioning
confidence: 99%
“…The confluence of these stresses and factors, along with the occurrence of other specific stressful life events, may put these students at high risk for DE. A global systematic review that included 89 studies with a total sample of 149,629 university students reported worrisome findings that about 20% of samples exhibited a high level of DE and could be classified at risk of developing a clinical eating disorder (Alhaj et al, 2022). This observation highlights the need for more research on DE in this population and its associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…Noting the lack of a previously agreed upon definition of DE and thus the lack of research data about its point prevalence, Levine and Smolak [ 11 ] estimated 15–20%, based on studies of either the prevalence of individual ED symptoms or the percentage of people scoring above cut-offs on measures such as the Eating Attitudes Test (EAT). Our recent meta-analysis of 89 studies of SBDE in university students, conducted in 40 countries and territories ( K = 105, N = 149,629), yielded a prevalence of 19.7% [ 12 ]. However, there was significant heterogeneity in the point prevalence of SBDE as a function of the type of measure.…”
Section: Introductionmentioning
confidence: 99%
“…To address this confusing state of affairs and to extend our previous meta-analytic reviews of SBDE in older adolescents and emerging adults [ 12 , 61 ], we conducted a meta-analysis of the global prevalence of SBDE in high school students. To the best of our knowledge, based on searches of the literature or other registration platforms, this is the first such meta-analysis of DE and potential moderators/confounders in this population.…”
Section: Introductionmentioning
confidence: 99%